Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-19T17:52:01+01:00
M1 = 4 kg
m2 = 6 kg
g = 9,81 m/s^2= 10 m/s^2
a = ?

m1*g + m1 *a = m2*g - m2 *a
m1*a + m2 *a = m2 *g - m1 *g
a (m1+m2) = g (m2 - m1)

a = g(m2 - m1) /m1+m2

a = 10 m/s^2 * 2 kg/10 kg

a = 2 m/s^2
1 5 1
2010-03-19T18:10:09+01:00
M1 = 4 kg
m2 = 6 kg
g = 9,81 m/s^2= 10 m/s^2
a = ?
m1*g + m1 *a = m2*g - m2 *a
m1*a + m2 *a = m2 *g - m1 *g
a (m1+m2) = g (m2 - m1)
a = g(m2 - m1) /m1+m2
a = 10 m/s^2 * 2 kg/10 kg
a = 2 m/s^2

Licze na najlepsze:).
3 5 3